Regional Structural Change and Resilience: From Lignite Mining to Tourism in the Lusatian Lakeland - Lintz, Gerd; Wirth, Peter; Harfst, Jörn (Raumforschung und Raumordnung | Spatial Research and Planning, 2012)
The terms “resilience” and “vulnerability” have both acquired prominence in recent academic and political debate. Originating in the natural sciences, they have meanwhile established themselves not only in the social sciences, but also—and more recently—in the areas of economic geography, as well as urban and regional development. Nevertheless, as is the case with many of the issues adopted from the natural sciences, the social sciences have had to struggle to fully capture and conceptualise the theoretical meaning of the terms. The present article will explore the added-value and limits of using the notions of resilience and vulnerability in relation to structural change in old industrial regions. It will also draw on empirical information from a qualitative case study of Lusatian Lakeland, a former lignite mining region in Eastern Germany that is currently being turned into a tourist destination. Research focuses on analysing the sectoral and regional cooperation between various actors in the region. The introduction of the terms resilience and vulnerability in this case study raises some interesting questions about the nature and interpretation of regional development processes that are characterised by a high degree of uncertainty and severe structural change. The research results also highlight the conceptual difficulties these terms present, particularly in the context of structural transformation.